The Role of Trauma and Stressful Life Events among Individuals at Clinical High Risk for Psychosis: A Review - Mayo, Danessa; Corey, Sarah; Kelly, Leah H.; Yohannes, Seghel; Youngquist, Alyssa L.; Stuart, Barbara K.; Niendam, Tara A.; Loewy, Rachel L. (Frontiers in Psychiatry, 2017)
The experience of childhood trauma and stressful life events is associated with subsequent development of a variety of mental health conditions, including psychotic illness. Recent research identifying adolescents and young adults at clinical high-risk (CHR) for psychosis allows for prospective evaluation of the impact of trauma and adverse life events on psychosis onset and other outcomes, addressing etiological questions that cannot be answered in studies of fully psychotic or nonclinical populations. This article provides a comprehensive review of the current emerging literature on trauma and adverse life events in the CHR population. Up to 80% of CHR youth endorse a lifetime history of childhood traumatic events and victimization (e.g. bullying). Several studies have shown that the experience of childhood trauma predicts psychosis onset among CHR individuals, while the literature on the influence of recent stressful life events (e.g. death of a loved one) remains inconclusive. Multiple models have been proposed to explain the link between trauma and psychosis, including the stress-vulnerability and stress-sensitivity hypotheses, with emphases on both cognitive processes and neurobiological mechanisms (e.g. the hypothalamic-pituitary-adrenal axis). Despite the preponderance of CHR individuals who endorse either childhood trauma or stressful life events, no clinical trials have been conducted evaluating interventions for trauma in CHR youth to date. Furthermore, the current process of formal identification and assessment of trauma, stressful life events and their impact on CHR youth is inconsistent in research and clinical practice. Recommendations for improving trauma assessment, treatment, and future research directions in the CHR field are provided.